Genomics and transcriptomics of the green mussel explain the durability of its byssus - Inoue, Koji; Yoshioka, Yuki; Tanaka, Hiroyuki; Kinjo, Azusa; Sassa, Mieko; Ueda, Ikuo; Shinzato, Chuya; Toyoda, Atsushi; Itoh, Takehiko (Scientific reports, 2021)
Mussels, which occupy important positions in marine ecosystems, attach tightly to underwater substrates using a proteinaceous holdfast known as the byssus, which is tough, durable, and resistant to enzymatic degradation. Although various byssal proteins have been identified, the mechanisms by which it achieves such durability are unknown. Here we report comprehensive identification of genes involved in byssus formation through whole-genome and foot-specific transcriptomic analyses of the green mussel, Perna viridis . Interestingly, proteins encoded by highly expressed genes include proteinase inhibitors and defense proteins, including lysozyme and lectins, in addition to structural proteins and protein modification enzymes that probably catalyze polymerization and insolubilization. This assemblage of structural and protective molecules constitutes a multi-pronged strategy to render the byssus highly resistant to environmental insults.